María Zambrano, la révélation de la naissance - Jean Marc Sourdillon (Cahiers de Civilisation Espagnole Contemporaine)
María Zambrano defines the concept of revelation as a kind of knowledge gained from experience. It appears often as a vision, it doesn’t accept rationalization, and it can only be translated only into a poetic language. María Zambrano, in her autobiographical works, discovers that revelation in her own life. In three different personal experiences –disease, exile, mourning– she finds the outlines of an intuition: life as a discontinued birth. The image of the dawn appears as the perfect representation of this intuition.